2019
DOI: 10.3748/wjg.v25.i21.2675
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use increases hepatic encephalopathy risk: A systematic review and meta-analysis

Abstract: BACKGROUND Several studies have been conducted to explore the association between the use of proton pump inhibitors (PPIs) and hepatic encephalopathy (HE) risk in patients with liver cirrhosis. However, their results are controversial. AIM To perform a systematic review and meta-analysis to evaluate the HE risk among PPI users. METHODS A systematic search on PubMed, Web of Science, EMBase, and ScienceDirect databases was conducted up to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…PPI use increases the risk of developing HE in patients with cirrhosis [104] as well as the severity of HE [105]. Two recent meta-analyses confirmed the association [106,107] and the proposed mechanism is that PPIs induce bacterial overgrowth in the intestine [108]. It is known that PPIs do not only change the bacterial composition in the stomach, but also in faeces with a significant shift towards oral flora in principal coordinate analyses (PCoA) [109,110], demonstrating that the entire gastrointestinal tract is affected downstream of gastric hypoacidity.…”
Section: Resultsmentioning
confidence: 99%
“…PPI use increases the risk of developing HE in patients with cirrhosis [104] as well as the severity of HE [105]. Two recent meta-analyses confirmed the association [106,107] and the proposed mechanism is that PPIs induce bacterial overgrowth in the intestine [108]. It is known that PPIs do not only change the bacterial composition in the stomach, but also in faeces with a significant shift towards oral flora in principal coordinate analyses (PCoA) [109,110], demonstrating that the entire gastrointestinal tract is affected downstream of gastric hypoacidity.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the impaired intestinal epithelial barrier in patients with cirrhosis [44] may facilitate the translocation of the overgrown bacteria to mesenteric lymph nodes, which finally leads to SBP and other infections [45]. Moreover, PPIs may also contribute to the gut dysbiosis that generally exists in patients with cirrhosis, whereas altered gut microbiota can induce or exacerbate HE [46,47], another complication that has been related to increased mortality risk in cirrhotic patients [12]. In addition, studies in overall population showed that PPI use may be associated with increased risks of cardiovascular adverse events [48], stroke [49], and fractures [50], which may also lead to increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, the indications and clinical efficacy of PPIs in these patients remain to be validated, which highlights the possible overutilization of PPIs in patients with cirrhosis [5]. Subsequently, increasing evidence from epidemiological studies indicated that PPI use may be associated with adverse outcomes in cirrhotic patients, spontaneous bacterial peritonitis (SBP) [6][7][8][9][10][11], and hepatic encephalopathy (HE) [12,13]. However, it remains unknown whether PPI use affects mortality in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a case‐control study in Taiwan, it was shown that PPI use increases the risk of HE development in a dose‐dependent fashion . Furthermore, a recent meta‐analysis including 7 trials with 4574 patients confirmed that PPI use increases the risk of HE development in cirrhotic patients …”
Section: Pathophysiologymentioning
confidence: 97%